Determination of aflatoxins in foodstuffs employing fluorometric method - Dimitrieska-Stojković Elizabeta D. (Zbornik Matice Srpske za Prirodne Nauke, 2005)
Results from the examination of total aflatoxins in foodstuffs are presented Determination of the aflatoxins was done employing rapid and reliable method based on immunnosorbent columns clean-up and measurement of the aflatoxins by fluorometer (Vicam, USA). Quantification and detection limits of the method were 1.0 and 0.1 ppb respectively. This method is especially suitable when laboratories are dealing with big number of samples. 20% of the samples were found to content total aflatoxins over MRL (5 g/kg). The positive samples were further analysed with TLC as a confirmatory method, whereby over 95% of positive samples where confirmed by TLC technique. Application of this rapid aflatoxin method significantly simplifies their analysis, especially when laboratories are dealing with big number of samples.